Encouraged by the scriptures: essays on scripture, interpretation, and life - Stylianopoulos, Theodore G. (Holy Cross Orthodox Press, 2011)
Christ the life of the world -- Orthodox biblical interpretation -- Scripture in St. Symeon the new theologian -- Sacred Scripture and Christian unity -- Concerning the biblical foundation of primacy -- Orthodox readings of Paul -- Vocation according to Paul -- Suffering according to Paul -- Grace and judgment in the book of Revelation